Matematisk kompetanse: I dybden på resultater fra PISA 2022 - Pettersen, Andreas; Jensen, Fredrik; Lid Berget, Ingeborg; Kaarstein, Hege; Løvgren, Maria; Mosvold, Reidar; Nilsen, Trude; Nortvedt, Guri A; Radišić, Jelena; Senneset, Marte K (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2024)
The results of the Programme for International Student Assessment (PISA) 2022 survey were published in a short report in the autumn of 2023. The report generated a great deal of interest in Norway, mainly due to Norwegian students’ poor performance in mathematics. In this anthology, the authors further analyze of the mathematics results in PISA 2022 and previous PISA surveys. The authors examine various aspects of the students’ mathematical competence, the core content of mathematics as a subject and they ways in which it is taught. In addition, they examine the extent to which Norwegian students have equal opportunities to master mathematics by looking more closely at characteristics of students who do poorly in mathematics and the significance of socio-economic background to student achievement levels. The results are discussed in a Norwegian school context and in light of the PISA 2022 results for the other Nordic countries, the LK20 curriculum and the COVID-19 pandemic as well as other current research. Some of the chapters have a didactic profile aimed at teachers, student teachers and school leaders, while other chapters are aimed more at researchers, politicians and decision-makers. Hovedresultatene fra PISA-undersøkelsen 2022 ble publisert i en kortrapport høsten 2023. Rapporten fikk mye oppmerksomhet, hovedsakelig på grunn av de norske elevenes svake prestasjoner i matematikk. I denne antologien gjør forfatterne videre analyser av matematikkresultatene fra PISA 2022 og tidligere PISA-undersøkelser. Forfatterne undersøker ulike sider ved elevenes matematiske kompetanse, innholdet i matematikkfaget og matematikkundervisningen. I tillegg undersøker de i hvilken grad norske elever har like muligheter til å lykkes i matematikk, ved å se nærmere på hva som kjennetegner de lavtpresterende elevene i matematikk, og hvilken betydning sosioøkonomisk status har for elevenes prestasjoner. Resultatene diskuteres i en norsk skolekontekst og blir sett i lys av resultater for de andre nordiske landene, læreplanen LK20, covid-19-pandemien og annen aktuell forskning. Noen av kapitlene har en didaktisk profil rettet mot lærere, lærerstudenter og skoleledere, mens andre kapitler i større grad er rettet mot forskere, politikere og beslutningstakere.